Demographic Factors and Test Anxiety among Secondary School Students - Michael Adeniyi Omoyemiju (Universitas Pendidikan Indonesia (UPI), 2023)
The study determined the level of test anxiety among secondary school students in Ilesa East Local Government Area (LGA) of Osun State, Nigeria. It also examined the association between students’ demographic factors and test anxiety in the study area. The study population comprised all Senior Secondary School (SSS) III students in the LGA. A sample of 240 students was selected by stratified sampling technique using school ownership (public and private) as a stratum. An adapted questionnaire titled Students’ Test and Examination Anxiety Measure (STEAM) was used to collect data for the study. The result showed that 50.8% of the respondents had a low level of test anxiety while 49.2% of respondents have a high level of test anxiety, and there was no statistically significant influence on students’ gender (Wald Χ2 = 0.000, p 0.05) on test anxiety. The study concluded that test anxiety is a physiological condition commonly exhibited by students irrespective of gender. It is recommended that any policy intervention programme to be developed either by the government or private organizations must not be gender biased.